Oral Mucosal Epithelial Cells - Groeger, Sabine; Meyle, Joerg (Frontiers in Immunology, 2019)
Cellular phenotype and apoptosis The function of epithelial tissues is protection of the organism from physical, chemical, and microbial damage which is essential for survival. To perform this function, oral epithelial cells undergo a well-regulated differentiation program resulting in the expression of structural proteins that maintain integrity of epithelial tissues and operate as a protective barrier. Oral epithelial cells are connected by various transmembrane proteins with specialised structures and functions. Keratin filaments are attached to the plasma membrane by desmosomes building a three-dimensional matrix. It is known that pathogenic oral bacteria may influence the expression and structural integrity of cell-cell junctions. Cellular receptors Cell-surface located toll like receptors (TLRs) and cytoplasmatic nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs) belong to the pattern recognition receptors (PRRs). PRRs recognize microbial components formed as pathogen-associated molecular patterns (PAMPs). Upon activation, a subset of NLR, initiate the assembly of a multimeric protein complex known as inflammasome, which processes pro-inflammatory cytokines. Cytokine production and release Cytokines and bacterial products may lead to host tissue destruction. Keratinocytes are able to produce diverse pro-inflammatory cytokines and chemokines, including Interleukin (IL)-1, IL-6, IL-8 and tumor necrosis factor (TNF)-α. Infection with pathogenic bacteria such as Porphyromonas gingivalis (P. gingivalis) and Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans) can induce production of these cytokines. Immunomodulation Human keratinocytes were shown to up-regulate immune-modulatory receptors upon stimulation with bacterial components. Periodontal pathogens including P. gingivalis are able to suppress innate immune responses of oral epithelial cells through different mechanisms and to evade host immune response, which results in persistent periodontal infection and furthermore are able to affect epithelial barrier function by altering expression and distribution of cell-cell interactions including tight junctions (TJs) and adherens junctions (AJs). Bacterial infection and cancer cells There is a known association between bacterial infection and cancer. Bacterial are able to up-regulate immune-modulatory receptors. Interactions of bacteria with tumor cells could favour the development of malignant transformed cells in an environment with dysregulated immune clearance. The aim of this review is to present a set of molecular mechanisms that enable oral epithelial cells to react to various exogenous possible noxious substances.